Specific Analysis and State Asset Management’s Efficiency Assessment Methods - E. А. Isaev; Е. А. Fedchenko; L. V. Gusarova; I. M. Van’kovich (Управленческие науки, 2021)
The Russian practice of control activities requires the formation of a modern concept of analyzing the effectiveness of the state (municipal) property use. The purpose of the article is to develop specific methods of property valuation. The authors practice methods of the empirical research, comparative and statistical research, synthesis of theoretical and practical material. Methods of grouping and classification have been used in the processing and systematization of information. The paper describes new approaches to the system of private and consolidated indicators of the efficiency of the asset management, taking into account the specifics of the public sector. Also, there are outlined the processes that ensure the achievement of the target indicators and maximization of the assessment of the property use. Utilization of the indicators system is going to form conclusions about the degree of a property use for making timely management decisions.